DESAIN GRAFIS SEBAGAI MEDIA UNGKAP PERIKLANAN - Sofyan Mufti Prasetiyo; Helda Sanira; Dian Ismiyati; Muhammad Syaiful Karim (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Graphic design was born from the human need for communication through visual language from the 19th century to modern times. Starting from the use of simple symbols to sophisticated computer devices. Design that is rooted in pure art which then develops into the functions of identification, information, instructions as well as Promotion and Presentation. Graphic design is a medium for conveying information through the language of visual communication in a two-dimensional or three-dimensional form that involves aesthetic principles. The main design elements involved in graphic design are ingredients in the form of: lines, letters, shapes and textures. Meanwhile, the structure is the organization of these design elements. A good design structure is the result of accurate integration of design principles in the placement process. The main design principles consist of: balance (balance), contrast, unity, value (value) and color. As a result of the interaction process with the world of art, socio-culture, industry and commerce, the various styles or styles of graphic design are getting richer and more colorful.